2015
DOI: 10.1044/2015_jslhr-s-14-0299
|View full text |Cite
|
Sign up to set email alerts
|

Effect Size for Single-Subject Design in Phonological Treatment

Abstract: Purpose The purpose of this study was to document, validate, and corroborate effect size (ES) for single-subject design in treatment of children with functional phonological disorders; to evaluate potential child-specific contributing variables relative to ES; and to establish benchmarks for interpretation of ES for the population. Method Data were extracted from the Developmental Phonologies Archive for 135 preschool children with phonol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 68 publications
0
30
0
1
Order By: Relevance
“…We Each article was scored for only one operational definition and one measurement system. Thus, the sum of operational definitions and the sum of measurement systems are each equal to the number of studies (12) FA functional analysis, SR reinforcer, FT fixed time, NA not applicable next conducted a k-cluster analysis (Gierut et al, 2015) to partition the remaining 15 effect sizes into three groups (small, medium, and large; Table 4). The majority of effect sizes in the current review were situated in the lowest of the three designated groups.…”
Section: Functional Analysis Results and Interventionmentioning
confidence: 99%
“…We Each article was scored for only one operational definition and one measurement system. Thus, the sum of operational definitions and the sum of measurement systems are each equal to the number of studies (12) FA functional analysis, SR reinforcer, FT fixed time, NA not applicable next conducted a k-cluster analysis (Gierut et al, 2015) to partition the remaining 15 effect sizes into three groups (small, medium, and large; Table 4). The majority of effect sizes in the current review were situated in the lowest of the three designated groups.…”
Section: Functional Analysis Results and Interventionmentioning
confidence: 99%
“…The PCC-R (4) index was applied in several studies that aimed to analyze speech impairment in children with SSD, both at diagnosis (10,14,16) and in treatment progression (13) . In particular, several studies with Brazilian Portuguese speakers have shown significant differences in PCC-R values as they compared children with and without SSD at different ages (8,(17)(18)(19) .…”
Section: Discussionmentioning
confidence: 99%
“…The latter index has been widely cited in the literature in order to verify its efficacy in classifying the degree of speech impairment in speech sound disorder (8)(9)(10)(11)(12)(13) . However, there is no age curve that demonstrates progress by means of its values and that makes it possible to verify if a child, at a certain age, is found within the expected value or not, which would aid identification of speech sound disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For example, greater production accuracy, learning, and generalization are associated with highfrequency words as compared with low-frequency words; high-frequency words are thus recommended as stimuli of treatment. [35][36][37] Similarly, words that are late acquired facilitate greater phonological learning and generalization as compared with other early acquired words; late acquired words are likewise recommended for treatment. 37,38 On the other hand, the findings from other studies reveal asymmetries that, although puzzling, open the door for future research.…”
Section: Which Words Boost Phonological Learning?mentioning
confidence: 99%